(untitled) (Revista Latino-Americana de Enfermagem, 2011)
This integrative review investigates how nurses plan the hospital discharge of patients with Congestive Heart Failure (CHF) since an inadequate discharge plan and patients subsequent non-adherence to instruction provided upon discharge are indicated as potential factors for re-hospitalization. A total of 24 papers were found in a search carried out in the LILACS and MEDLINE databases between 2004 and 2008, which given the inclusion criteria, were reduced to 14 papers. The papers were analyzed and categorized into Health Education, and Nursing Care. The synthesis of results indicates that the discharge plan devised by nurses is based on two categories. The actions of nurses to promote health education can enable patients with CHF to improve self-care.